Knowledge and attitude factors associated with the prevalence of Tdap (tetanus, diphtheria, and acellular pertussis) booster vaccination in healthcare workers in a large academic hospital in Southern Italy in 2022: a cross-sectional study - Mercogliano, Michelangelo; Fiorilla, Claudio; Esposito, Federica; Sorrentino, Michele; Mirizzi, Pasquale Domenico; Parisi, Antonio; Tajani, Andrea; Buonocore, Gaetano; Triassi, Maria; Palladino, Raffaele (Frontiers in Public Health, 2023)
In Europe, there is still suboptimal Tetanus, diphtheria, acellular pertussis (Tdap) booster coverage. The aim of this study was to assess coverage status, knowledge, and attitude on Tdap vaccination in healthcare workers (HcWs) of the University Hospital "Federico II" in Naples, Southern Italy, in 2022, to improve current vaccination strategies.A cross-sectional study was conducted using a validated anonymous questionnaire. Knowledge and attitude were measured as scores. Multivariable logistic and linear regression models were employed to identify correlates of Tdap booster and knowledge and attitude towards the vaccination, as appropriate. Models were controlled for age, sex, profession, department, and job seniority. 206 questionnaires were administered among HcWs, 143 (69.4%) were medical doctors. 71 (34,47%) HcWs received the Tdap booster. Those who have worked 5-9 years at the hospital had a 78% lower likelihood of being vaccinated with the Tdap booster (5-9 years -OR: 0.22, CI: 0.06 | 0.85) as compared with newly hired HcWs. No differences in the average knowledge score were found. Medical doctors had a higher attitude towards vaccination than other HcWs (Other -Coef. -2.15; CI: -4.14 | -0.15) and, as compared with those who worked in a clinical department, those who worked in a diagnostic-therapeutic department or in a medical management had a 3.1 and 2.0 lower attitude This is a provisional file, not the final typeset article score, on average, respectively (diagnostic-therapeutic -Coef. -3.12, CI: -5.13 | -1.12; public health -Coef. -1.98, CI: -3.41 | -0.56).The study findings support the necessity to implement public health strategies and improve knowledge and attitude toward vaccinations, and specifically highlight the importance of Tdap booster every 10 years as prevention tool to protect high-risk populations.